A new approach for measuring the operational value of intelligence for military operations : final report - Cesar, Edison, 1924-; Allen, Patrick D.; Bankes, Steven C.; Bondanella, J. (John), 1944-; Eden, Rick, 1954-; Hall, Edward Twitchell, 1914-; Veit, Clairice T.; Verma, Loretta; Weissler, Robert; Wilson, Barry, 1959-; Rand eBooks (Santa Monica, CA : RAND, 1994)
Policymakers have long needed an improved analytic basis for their investment decisions regarding military intelligence assets. This report presents a new methodology for measuring the operational value of military intelligence, electronic warfare, and target acquisition (IEW/TA) and also describes two prototype models for studying IEW/TA in an operational context. The methodology enables the operational value of intelligence assets and activities to be expressed in quantifiable terms useful to resource acquisition decisionmakers, military planners, and operational managers. One application of the methodology is to help build the intelligence portion of the Army five-year program. The two prototype models were designed as aids for performing policy and other analysis of key issues. One is a spreadsheet model that can be used to assess the operational value of a given IEW/TA architecture at a point in time under various conditions; the other is a dynamic simulation that can be used to study how the value of IEW/TA changes through the course of an operation.
"Arroyo Center."
Includes bibliographical references (p. 145-147).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Military intelligence -- United States -- Computer simulation; Electronic books